SINGLE SAMPLING PLANS FOR VARIABLES INDEXED BY AQL AND AOQL UNDER EWMA MODEL - Sankle, R.; Singh, J. R. (Journal of Reliability and Statistical Studies, 2012)
The objective of this paper is to provide expression for evaluating sample size(n), acceptance parameter(k), Average Outgoing Quality(AOQ) and Operating Characteristic(OC) function under Exponentially Weighted Moving Average (EWMA) model. The paper provides an investigation into the robustness of single sampling procedure indexed by Acceptance Quality Level(AQL) and Average Outgoing Quality Level(AOQL).